The dynamics of lowland river sections of Danube and Tisza in the Carpathian basin - Imre M. Jánosi; Imre M. Jánosi; István Zsuffa; István Zsuffa; Tibor Bíró; Boglárka O. Lakatos; Boglárka O. Lakatos; András Szöllősi-Nagy; Zsolt Hetesi; Zsolt Hetesi (Frontiers in Earth Science)
The paper presents a detailed statistical analysis of data from 41 hydrometric stations along the Danube (section in the Carpathian Basin) and its longest tributary, the Tisza River. Most records cover 2–3 decades with an automated high temporal sampling frequency (15 min), and a few span 120 years with daily or half-daily records. The temporal sampling is not even and exhibits strong irregularities. The paper demonstrates that cubic spline fits and down-sampling (where necessary) produce reliable, evenly sampled time series that smoothly reconstruct water level and river discharge data. Almost all the water level and discharge records indicate a decadal decreasing trend for annual maximum values. The timing (day of the year) for annual maxima and minima is evaluated. While minimum values do not show coherent tendencies, annual maxima exhibit increasing trends for the Tisza but decreasing trends for the Danube (earlier onset). Various possibilities for the explanations of these observations are listed. The empirical histograms for half-daily water level changes can be well-fitted by piecewise-exponential functions containing four or three sections, consistent with the understanding that level changes are deterministic rather than stochastic processes, as is well known in hydrology. Such statistical tests can serve as benchmarks for modeling water levels and discharges. Extracted periods by the Lomb-Scargle algorithm (suitable for unevenly sampled time series) and the long-time means indicate the expected annual seasonality. Resampled time series (1-hour frequency) were evaluated by standard Fourier and Welch procedures, revealing some secondary peaks in the spectra indicating quasi-periodic components in the signals. Further significance tests are in progress, along with attempts at explanations. Secondary peaks may indicate environmental changes, the future investigation of which could reveal important correlations.